2003
DOI: 10.1139/g02-107
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microsatellites in wild and sweet cherry (Prunus avium L.) — markers for individual identification and reproductive processes

Abstract: Nuclear microsatellites were characterized in Prunus avium and validated as markers for individual and cultivar identification, as well as for studies of pollen- and seed-mediated gene flow. We used 20 primer pairs from a simple sequence repeat (SSR) library of Prunus persica and identified 7 loci harboring polymorphic microsatellite sequences in P. avium. In a natural population of 75 wild cherry trees, the number of alleles per locus ranged from 4 to 9 and expected heterozygosity from 0.39 to 0.77. The varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 26 publications
8
45
1
Order By: Relevance
“…There were 4 alleles identified in the peach sequenced UDP96-019 locus developed by Cipriani et al (1999), whereas there were 6 alleles identified at this locus in the plum accessions. While 6 alleles were detected in the peach sequenced (Cipriani et al, 1999) UDP96-005 SSR locus in their study on 84 wild cherry genotypes (Schueler et al, 2003), in the current study, the locus produced 6 alleles. There were 11 alleles (H O = 0.516) detected in the UDAp-404 locus used in the current study for the genetic analyses of the plum accessions, and the number of alleles was higher compared to the study by Messina et al (2004) (who developed this locus) on apricot genotypes (6 alleles, H O = 0.44).…”
Section: Discussioncontrasting
confidence: 54%
“…There were 4 alleles identified in the peach sequenced UDP96-019 locus developed by Cipriani et al (1999), whereas there were 6 alleles identified at this locus in the plum accessions. While 6 alleles were detected in the peach sequenced (Cipriani et al, 1999) UDP96-005 SSR locus in their study on 84 wild cherry genotypes (Schueler et al, 2003), in the current study, the locus produced 6 alleles. There were 11 alleles (H O = 0.516) detected in the UDAp-404 locus used in the current study for the genetic analyses of the plum accessions, and the number of alleles was higher compared to the study by Messina et al (2004) (who developed this locus) on apricot genotypes (6 alleles, H O = 0.44).…”
Section: Discussioncontrasting
confidence: 54%
“…The standard protocol was modified by using 40 ml of NaOH and 95 ml of Tris buffer for each sample. Samples were genotyped at six microsatellite loci that were originally developed for Prunus avium and Prunus persica: UDP97-403 (Cipriani et al, 1999), P12A02 (Sosinski et al, 2000), BPPCT-002 (Dirlewanger et al, 2002), UDP96-005 and UDP98-410 (Schueler et al, 2003), and EMPaS06 (Vaughan and Russell, 2004). …”
Section: Molecular Analysesmentioning
confidence: 99%
“…The DNA was quantified on a NanoDrop system (Thermo Fisher Scientific, Schwerte, Germany) and diluted to a standardized DNA concentration of 10 ng ml À1 . We amplified eight microsatellite loci (Testolin et al, 2000;Dirlewanger et al, 2002;Schueler et al, 2003), using the combinations and conditions described in , with the only difference being the labelling from primers UDP98_411 (FAM), UDP98_412 (FAM) and BPPCT_040 (HEX). Fragments were analysed on a Megabace genetic analyser (Amersham Biosciences, Buckinghamshire, UK) using the Megabace ET 400-R size standard (GE Healthcare, Munich, Germany).…”
Section: Genetic Analysismentioning
confidence: 99%